2011
DOI: 10.1002/hlca.201000285
|View full text |Cite|
|
Sign up to set email alerts
|

Three New Triterpenoid Saponins from Ardisia crenata

Abstract: Three new triterpenoid saponins, ardisicrenoside I (1), ardisicrenoside J (2), and ardisicrenoside M (3), along with eight known compounds, were isolated from the roots of Ardisia crenata Sims. Their structures were elucidated as 16α‐hydroxy‐30,30‐dimethoxy‐3β‐O‐{β‐D‐xylopyranosyl‐(1→2)‐β‐D‐glucopyranosyl‐(1→4)‐[β‐D‐glucopyranosyl‐(1→2)]‐α‐L‐arabinopyranosyl}‐13β,28‐epoxyoleanane (1), 16α‐hydroxy‐30,30‐dimethoxy‐3β‐O‐{α‐L‐rhamnopyranosyl‐(1→2)‐β‐D‐glucopyranosyl‐(1→4)‐[β‐D‐glucopyranosyl‐(1→2)]‐α‐L‐arabinopyra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Although compounds can be identified through GC, analyzing triterpenes, including the analytes with low volatility, remains a challenge because it requires transformation in trimethylsilyl derivatives. Liu et al [78] evaluated the cytotoxic activities of triterpenes (ardisicrenoside O, P, and Q) on two human cancer cell lines, with the application of GC-MS to qualification of the compounds. They discovered that ardisicrenoside Q, which was a pentacyclic triterpenoids existed in the roots of Ardisia crenata, had significant cytotoxicity.…”
Section: Gcmentioning
confidence: 99%
“…Although compounds can be identified through GC, analyzing triterpenes, including the analytes with low volatility, remains a challenge because it requires transformation in trimethylsilyl derivatives. Liu et al [78] evaluated the cytotoxic activities of triterpenes (ardisicrenoside O, P, and Q) on two human cancer cell lines, with the application of GC-MS to qualification of the compounds. They discovered that ardisicrenoside Q, which was a pentacyclic triterpenoids existed in the roots of Ardisia crenata, had significant cytotoxicity.…”
Section: Gcmentioning
confidence: 99%
“…[2] A. crenata Sims is a genus of plants in the myrtle family Ardisia, and its roots are recorded in the Chinese Pharmacopoeia (2020) edition for a commonly used as Chinese medicine "Zhushagen". The roots are commonly used for the treatment of sore throat, dysmenorrhea and rheumatism, [3][4][5] and research on chemical constituents showed that triterpenoid saponins, isocoumarins, phenols and benzoquinones were the main chemical constituents in A. crenata Sims, [6][7][8] and studies on these chemical constituents found that triterpenoid saponins had better anti-tumour activity. [9] Moreover, lactones are rarely isolated in A. crenata Sims, and this kind of active ingredients often have better antiinflammatory activities.…”
Section: Introductionmentioning
confidence: 99%
“…The Ardisia crenata Sims is a common evergreen shrub belonging to Ardisia of Myrsinaceae with red fruits at maturity [ 3 ]. In China, the roots of the red-fruited A. crenata Sims are used as a traditional Chinese medicine “Zhushagen” [ 4 ], which is widely used for the treatment of respiratory infections, toothache, arthralgia, menstrual problems, and fertility regulation [ 5 , 6 , 7 ]. These pharmacological activities are often closely related with different kinds of chemical constituents from the roots of A. crenata Sims.…”
Section: Introductionmentioning
confidence: 99%